ANALISA SIFAT MEKANIK PADUAN ALUMINIUM SEBAGAI RANGKA JENDELA KAPAL DI PERUSAHAAN PENGECORAN LOGAM CV. SETIA KAWAN KOTA TEGAL DENGAN CETAKAN TIDAK PERMANEN - Kiryanto, Kiryanto; Sasmito Hadi, Eko; Ansori, Muhammad (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2012)
Shiping components necessary are needed nowadays. For that many minor industry develop. One of them is CV. Setia Kawan Tegal City which is one of central metal cast company which main product is ship component but product that produced by CV. Setia Kawan has not comply but JIS or SNI standart. Based on that, this final project purposed to now tensil test and material composition include from the material that produced by CV. Setia Kawan. Materials which used is pure elbow Aluminium, Aluminium Plat, brake Canvas and used pan. Those materials must pass some process before tested, melting process, casting process than extracting from mould with use permanent mould. After that the next process which done is tensil test. Beside tensil test material also pass material composition test. Tensil test result shows that Aluminium and Break canvas has the best materials quallity and fullfell JIS and SNI standart about 13,18 kg/mm² for Aluminium Plate with used pan fusion about 10,46 kg/mm². Where as for elbow Aluminium and Aluminium Plate fot it about 8,84 kg/mm² and 10,33 kg/mm². For the materials composition test result with passed melting process, elbow aluminium and brake canvas and Aluminium Plate with used plan have fullfelled standart both JIS and SNI which each content about 92,46% and 99,43%. For elbow Aluminium and Aluminium Plate each content about 99,43% and 98,46% but material give not pass standart. Where as pure materilas has not passed melting process for Aluminium and Aluminium Plate doesn’t meet standart both have its content 98,33% and 99,59%. For breake canvas and used panthose about materials comply SNI and JIS standart with content 84,68% and 97,66%.